2018
DOI: 10.1039/c8ra02415d
|View full text |Cite
|
Sign up to set email alerts
|

Effects of area, aspect ratio and orientation of rectangular nanohole on the tensile strength of defective graphene – a molecular dynamics study

Abstract: Molecular dynamics simulations with adaptive intermolecular reactive empirical bond order (AIREBO) potential are performed to investigate the effects of rectangular nanoholes with different areas, aspect ratios (length/width ratios) and orientations on the tensile strength of defective graphene. The simulations reveal that variation of area, aspect ratio and orientation of rectangular nanohole can significantly affect the tensile strength of defective graphene. For example, defective graphene with a larger … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…The distinctive difference in ∆z distortion at 5% compressive strain (and the lack thereof at 2% compressive strain) can be explained by the simple notion that graphene's elasticity becomes anisotropic for both armchair and zigzag directions as a function of strain [42,43,44]. The anisotropic behaviour of the Γ -K (zigzag) and Γ -M (armchair) directions at 5% compressive strain (and the lack thereof at 2% compressive strain) furthermore suggests that the ripple formation process under isotropic compression is based on two competing effects, a) the energy gain through out-of-plane ∆z distortions (rippling) and b) the elasticity of the sheet, which varies with direction and strain [42,43,44]. Based on the formalism of reference [44], we can therefore express the ripple formation energy as…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The distinctive difference in ∆z distortion at 5% compressive strain (and the lack thereof at 2% compressive strain) can be explained by the simple notion that graphene's elasticity becomes anisotropic for both armchair and zigzag directions as a function of strain [42,43,44]. The anisotropic behaviour of the Γ -K (zigzag) and Γ -M (armchair) directions at 5% compressive strain (and the lack thereof at 2% compressive strain) furthermore suggests that the ripple formation process under isotropic compression is based on two competing effects, a) the energy gain through out-of-plane ∆z distortions (rippling) and b) the elasticity of the sheet, which varies with direction and strain [42,43,44]. Based on the formalism of reference [44], we can therefore express the ripple formation energy as…”
Section: Resultsmentioning
confidence: 99%
“…It was found that a compressive strain of 5% gives a similar corrugation pattern to that obtained in experiments. Various studies have also shown that the elasticity of graphene varies with direction (see Figure 2) [42,43,44]. For example, previous studies have shown that armchair graphene nanoribbons (GNRs) have a higher Young's Modulus, tensile fracture stress and strain than zigzag GNRs of the same size [42,43].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Qin et al. [ 53 ] explored the impact of vacancy‐defect containing area, aspect ratio, and tilting angle of nanohole on the tensile strength of graphene by MD simulations and quantized fracture mechanics. Figure 2d1 shows the tensile strengths of defective zigzag and armchair graphene declined with the increasing area of rectangular nanohole.…”
Section: Strengthening and Toughening Of Graphene/polymer Nanocompositesmentioning
confidence: 99%
“…Reproduced with permission. [ 53 ] Copyright 2018, Royal Society of Chemistry. e1,e2) The effect of size on the mechanical properties of armchair and zigzag graphene nanoribbon.…”
Section: Strengthening and Toughening Of Graphene/polymer Nanocompositesmentioning
confidence: 99%